North Atlantic Regional Water Resources Study. Appendix A. History of Study. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
The history of the North Atlantic Regional Water Resources STudy is a brief description of its progress from authorization by Congress in 1965 to completion in 1972. This work is a chronology rather than a description of the Study as most definitive statements of the work during the Study are found in other sections of the Report, it Annexes and Appendices. The NAR Study required the coordination and cooperation of a great many Federal, state, interstate and local agencies under the direction of the Corps of Engineers, and the Coordinating Committee as the final authority. The major historical stages that form the basis of this Appendix are the steps taken to cement the partnership of the agencies to develop the various stages of plan formulation, and the publication of the Final REport. Appendix A to report dated Jun 72, AD-A036 616. See also Appendix B, AD-A036 620.